The Influence of Electronic Word of Mouth (E-Wom) on Customer Purchase Interest on the Shopee E-Commerce Social Site in Semper Barat Subdistrict - Salsabila, Amanda Aulia; Rustomo, Rustomo; Rahman, Erik (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aimed to analyze the influence of Electronic Word of Mouth (E-WOM) on interest buy customers on the e-commerce social site Shopee in West Semper Village . E-WOM has become factor important in digital marketing , especially on e-commerce platforms like Shopee. This study used method quantitative with technique data collection via distributed questionnaires to Shopee users in Semper Barat Subdistrict . Research sample A total of 40 respondents were selected use purposive sampling technique . Data analyzed use method analysis statistics simple linear regression . Research result show that E-WOM has influence significant to interest buy Shopee customers in West Semper Village . This study gave contribution theoretical in understand the role of E-WOM in e-commerce context in Indonesia, especially in urban areas such as West Semper Village . By practical , results This studycan become reference for perpetrator e-commerce business in designing effective marketing strategies with utilizing E-WOM.